2013
DOI: 10.1088/0953-2048/26/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Precursor superconducting diamagnetism in YBa2Cu3O7−δwith in-plane or intercalated magnetic impurities

Abstract: The magnetization around the superconducting transition was measured in YBa 2 Cu 3 O 7−δ with magnetic impurities in the CuO 2 layers (Cu substituted by Zn or Ni) or between them (Y substituted by Gd or Pr). While some of these impurities have an important effect on the superconducting transition temperature (T c ), the precursor diamagnetism observed above T c is not appreciably affected. This result contrasts with recent observations in a conventional BCS superconductor (La), in which the precursor diamagnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[11]). This is in fact the case of high-T c cuprates: recent measurements [12] have shown that the fluctuation diamagnetism of optimally-doped YBa 2 Cu 3 O 7−δ is not appreciably affected by the presence of magnetic impurities (both in the CuO 2 planes or intercalated between them). In striking contrast, the measurements in lanthanum with diluted magnetic (Pr) impurities presented in Ref.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[11]). This is in fact the case of high-T c cuprates: recent measurements [12] have shown that the fluctuation diamagnetism of optimally-doped YBa 2 Cu 3 O 7−δ is not appreciably affected by the presence of magnetic impurities (both in the CuO 2 planes or intercalated between them). In striking contrast, the measurements in lanthanum with diluted magnetic (Pr) impurities presented in Ref.…”
Section: Introductionmentioning
confidence: 95%
“…(For a recent theoretical work on this issue see, e.g., [11].) This is in fact the case with high-T c cuprates: recent measurements [12] have shown that the fluctuation diamagnetism (FD) of optimally doped YBa 2 Cu 3 O δ − 7 is not appreciably affected by the presence of magnetic impurities (either in the CuO 2 planes or intercalated between them). In striking contrast, the measurements in lanthanum with diluted magnetic (Pr) impurities presented in [13] have shown an important enhancement of FD, that is observed to be considerably larger than the theoretical results for three-dimensional isotropic superconductors [5,6,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%